Interpolation of the Measure of Non Compactness between Quasi-Banach Spaces - Fernández Martínez, Pedro (Revista Matemática Complutense, 2006)
We study the behavior of the ball measure of non-compactness under several interpolation methods. First we deal with methods that interpolate couples of spaces, and then we proceed to extend the results to methods that interpolate finite families of spaces. We will need an approximation hypothesis on the target family of spaces.